2016
DOI: 10.1021/acs.inorgchem.5b02740
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Substituents at Lewis Acidic Bismuth(III) Centers on Its Propensity to Bind a Noble Metal Donor

Abstract: To investigate the effect of X in ambiphilic compounds BiX(o-PPh2-C6H4)2, PBiP-X, on metallophilic Pt-Bi interactions in its PtCl2 complexes two new derivatives PBiP-Me and PBiP-C6F5 were synthesized. Reaction with dichloro(1,5-cyclooctadiene)platinum(II) led to the platinum(II) complexes [PtCl2(PBiP-Me)], 3, and [PtCl2(PBiP-C6F5)], 4, which together with the halide [PtCl2(PBiP-Cl)], 2, reported previously, establish a series of related PBiP-X complexes differing only in X. This could be complemented by access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…The Lewis acidity of Bi III in an ambiphilic PBiP ligand system (Ph 2 P‐C 6 H 4 ‐Bi(Cl)‐C 6 H 4 ‐PPh 2 ), employed as such or generated in situ, was exploited to bind Au I , Pt II and Pd II centers, which acted as σ donors. It was further shown that upon replacement of the Cl residue at Bi against less electronegative ligands, the character of the bismuthane changed from acceptor to predominantly donor …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The Lewis acidity of Bi III in an ambiphilic PBiP ligand system (Ph 2 P‐C 6 H 4 ‐Bi(Cl)‐C 6 H 4 ‐PPh 2 ), employed as such or generated in situ, was exploited to bind Au I , Pt II and Pd II centers, which acted as σ donors. It was further shown that upon replacement of the Cl residue at Bi against less electronegative ligands, the character of the bismuthane changed from acceptor to predominantly donor …”
Section: Figurementioning
confidence: 99%
“…character of the bismuthane changed from acceptor to predominantly donor. [7] The insights gained tethering bismuthane functions with phosphane units as in the PBiP ligand mentioned above for the complexation of late transition metals, led us to pursue further promisingb ismuthane/phosphane combinations. The xantheneb ackbone has been used for the construction of av ariety of potent bidentate ligands and complexes that exhibit interesting reactivity.…”
mentioning
confidence: 99%
“…At the top of the group (N and P) the higher electronegativity,c ombined with the presence of compact lone pairs,i sk nown to lead to ambidentate character in which both the N-atoms of the 2-py groups and the Group 15 atom (E) can donate to metal ions ( Figure 2b). [32][33][34][35][36] The increase in the Lewis acidity of the bridgehead atoms in 1-3 was demonstrated by initial DFT (B3LYP/def2-TZVPP) calculations of their fluoride ion affinities (see the Supporting Information). [32][33][34][35][36] The increase in the Lewis acidity of the bridgehead atoms in 1-3 was demonstrated by initial DFT (B3LYP/def2-TZVPP) calculations of their fluoride ion affinities (see the Supporting Information).…”
mentioning
confidence: 98%
“…NBO analysis has been shown by many groups to be highly useful when analyzing weak to moderate bonding interactions such as ligand-metal donor-acceptor interactions 53,54 and metallophilic interactions. 10,41,[55][56][57] The monomers corresponding to 1(Me) (1-mon), 1-H(Me) Table 4, the Wiberg Bond Indices are in Table 5, and second-order perturbation energies in Table 6. Inspection of these three tables shows that each of the theoretical methods reproduces the same trends, and the methods behave as expected.…”
Section: -H(me)mentioning
confidence: 99%